Economics and world history : myths and paradoxes - Bairoch, Paul. (Chicago : University of Chicago Press, 1993)
"Paul Bairoch deflates twenty commonly held myths about economic history. Among these myths are that free trade and population growth have historically led to periods of economic growth, and that colonial powers in the nineteenth and early twentieth centuries became rich through the exploitation of the Third World. Bairoch shows that these beliefs are based on insufficient knowledge and wrong interpretations of the history of economies of the United States, Europe, and the Third World, and he re-examines the facts to set the record straight." "Bairoch argues that until the early 1960s, the history of international trade of the developed countries was almost entirely one of protectionism rather than a "Golden Era" of free trade, and he reveals that, in fact, past periods of economic growth in the Western World correlated strongly with protectionist policy. He also demonstrates that developed countries did not exploit the Third World for raw materials during the nineteenth and early twentieth centuries, as some economists and many politicians have held. Among the many other myths that Bairoch debunks are beliefs about whether colonization triggered the Industrial Revolution, the effects of the economic development of the West on the Third World, and beliefs about the 1929 crash and the Great Depression." "Bairoch's lucid prose makes the book equally accessible to economists of every stripe, as well as to historians, political scientists, and other social scientists."--BOOK JACKET.
Pt. I. Major Myths About the Developed World -- 1. The 1929 Crash and the Great Depression -- 2. Was there a Golden Era of European Free Trade? -- 3. Was there Free Trade in the Rest of the World? -- 4. Has Protectionism Always had a Negative Impact? -- Pt. II. Major Myths on the Role of the Third World in Western Development -- 5. Were Third-World Raw Materials Central to Western Industrialization? -- 6. Were Colonial Outlets Crucial to Western Industries? -- 7. Was Colonialism Important in Triggering the Industrial Revolution? -- 8. The Balance Sheet of Colonialism -- Pt. III. Major Myths About the Third World -- 9. Was there a Large Income Differential before Modern Development? -- 10. A long-term Deterioration in the Terms of Trade? -- 11. The More Tropical Products Exported, the More Food Imported? -- 12. Population Growth: the More, the Better? -- Pt. IV. 'Minor' Myths and Unnoticed Turning Points -- 13. Some Less Important Myths -- 14. Generally Unnoticed Historical Turning Points. Conclusions: The Paradox of Economic History or the Absence of Absolute Economic Laws.
Includes bibliographical references and index.
Keywords: Economic history; Free trade -- History; Developing countries -- Economic conditions